REHABILITASI HUKUM BAGI KORBAN ERROR IN PERSONA DALAM SISTEM PERUNDANG-UNDANGAN INDONESIA - Nabella Difa Sabrina (Supremasi Hukum: Jurnal Penelitian Hukum, 2026)
This article examines the problem of error in persona within the Indonesian criminal justice system, namely the wrongful arrest or conviction of individuals who are in fact innocent. Although the Constitution and statutory regulations guarantee the protection of human rights, legal provisions governing rehabilitation for victims of error in persona remain very limited and are dispersed across various, non-integrated legal instruments. While several studies have addressed the issue of error in persona, this research offers a normative legal analysis focusing on the adequacy and coherence of legal regulations concerning the rehabilitation of victims of error in persona. The findings indicate that the existing rehabilitation mechanisms have not been able to provide optimal restoration of victims’ rights. This study employs a normative legal research method with a statutory approach by examining applicable laws and regulations. The results demonstrate the necessity of legal reform through the establishment of specific regulations that guarantee comprehensive recovery, including fair compensation, restoration of reputation, and psychosocial rehabilitation. Such reform is essential to strengthen the protection of citizens’ constitutional rights and to enhance the accountability of the criminal justice system in Indonesia.